A Double-Sided Board from Tell Afis - Dunn-Vaturi, Anne-Elizabeth (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
Problems of identification with gaming material often occur even when the object is complete. The game of 20 squares is no exception. A marble board from Tell Halaf discovered in the early 20th century ‘has been explained as an incense-burner, as a throne-altar upon which a bronze statuette might have been seated, or as the handle of a ceremonial fan’ before being identified as a gaming-board in the late 1930s (Van Buren 1937: 11-12, fig. 1, pl. VI). The challenge of identifying gaming material is even greater with fragmentary evidence. A greenstone plate from Tell Afis described as a cosmetic palette with sunken compartments on both sides (Mazzoni 2005: 57) should probably also be reinterpreted as a playing device (Figure 1).